A 3‐year longitudinal study of the association of physical activity and sedentary behaviours with childhood obesity in China: The childhood obesity study in China mega‐cities. Issue 6 (22nd November 2020) - Sun, Xiaomin; Zhao, Bingtong; Liu, Jin; Wang, Yun; Xu, Fei; Wang, Youfa; Xue, Hong
Summary: Objectives: Examine school children's physical activity (PA) and sedentary behaviours (SB) during 2015 to 2017 in China, and study their associations with children's weight status and relevant gender differences. Methods: This open cohort study included students from five major cities (Beijing, Shanghai, Xi'an, Nanjing, and Chengdu) across China. Data were collected from students in 2015, 2016, and 2017 ( n = 5535) and from their parents and school personnel. Children's weight, height, and waist circumference were measured. SB and PA factors were evaluated using questionnaires. Mixed‐effects models examined the relationship between weight status and PA‐/SB‐associated factors using this longitudinal data. Results: These children had high rates of obesity (12.4%, 95% CI 11.6%‐13.3%) and central obesity (28.1%, 95% CI 26.9%‐29.3%) during 2015 to 2017. Boys were more likely to have obesity than girls (16.5% vs 8.4%, respectively) as well as centrally obesity (36.3% vs 19.8%, respectively) and spent more time in screen viewing than girls (hours/week ± SD: 2015, 1.8 ± 2.5 vs 1.5 ± 2.0; 2016, 2.0 ± 2.4 vs 1.8 ± 2.5; 2017, 1.7 ± 2.3 vs 1.4 ± 2.1 hours/week). Those who walked <5 minutes on their average daily walk to school were more likely to have obesity (OR: 1.96, 95% CI 1.03‐3.73) than those who spent ≥15 minutes on walking to school. When stratified by gender, this higher risk was only observed in girls (OR: 3.01, 95% CI 1.09‐8.35). Children who spent more time in screen viewing were more likely to have obesity (OR: 1.13, 95% CI 1.06‐1.21) and have central obesity (OR: 1.05, 95% CI 1.02‐1.09). The association for obesity was consistent in boys and girls (boys, OR: 1.15, 95% CI 1.05‐1.25; girls, OR: 1.12, 95% CI 1.00‐1.24). Conclusions: More screen time and less walking time were risk factors for developing obesity in urban Chinese children. The associations varied by gender.